2004
DOI: 10.1111/j.1439-0426.2004.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction, growth, mortality and yield of Tilapia mariae Boulenger 1899 (Cichlidae) in a Nigerian rainforest wetland stream

Abstract: The biology and fisheries of Tilapia mariae, the only tilapiine cichlid fish in the Iba Oku (Uyo, Nigeria) wetland stream was studied. There were more females than males in the population. The smallest sexually mature female fish was 11.0 cm total length (TL) while the size at 50% maturity was 17.1 cm TL. Absolute fecundity (F e ) ranged from 953 to 3200 eggs and was positively correlated with TL. The fish bred year-round with peaks in November, March-April and July-September. The seasonalized von Bertalanffy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 15 publications
4
36
1
1
Order By: Relevance
“…The sex ratio of most fish species in the wild tends to be 1:1 but deviations can occur and seasonal variations are common (Helfman et al, 2009). The sex ratio is influenced by several factors, including mortality, longevity and growth rate; these in turn lead to differences in the catch rate (King and Etim, 2004;Novaes and Carvalho, 2012). The values of sex ratio in the present study are in accordance with that estimated by some authors for studied species and differ from others.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The sex ratio of most fish species in the wild tends to be 1:1 but deviations can occur and seasonal variations are common (Helfman et al, 2009). The sex ratio is influenced by several factors, including mortality, longevity and growth rate; these in turn lead to differences in the catch rate (King and Etim, 2004;Novaes and Carvalho, 2012). The values of sex ratio in the present study are in accordance with that estimated by some authors for studied species and differ from others.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…According to Sparre and Venema (1992), longevity is more closely related to mortality than growth curvature, asymptotic length or ambient temperature. Maximum age of 7 years was estimated for T. mariae (King & Etim, 2004). This difference could be attributed to K-values of the two species T. mariae had a lower growth curvature parameter, K, (0.4/year) than T. zillii in this study (K=0.81/year).…”
Section: Discussionmentioning
confidence: 78%
“…From the present study, the calculated Z/K ratio was greater than 1, suggesting that the stock is mortality dominated. King and Etim (2004) highlighted that for a mortality dominated stock, Z/K ratio ≈ 2 denotes a lightly-exploited stock while values greater than 2 shows heavy exploitation. With the estimated Z/K ratio highly greater than 2, it showed that Sardinella aurita stock in Ghana's coastal waters is heavily exploited.…”
Section: Discussionmentioning
confidence: 99%